Optoelectronic and charge‐transport properties of truxene, isotruxene, and its heteroatomic (N, O, Si, and S) analogs: A DFT study. (25th February 2019) - Tripathi, Anuj; Prabhakar, Chetti
Abstract: The main objective of this work is to provide a detailed study of optoelectronic and charge‐transport properties of truxene, isotruxene, and their heteroatomic analogs (azatruxene and isoazatruxene, oxatruxene and isooxatruxene, silatruxene and isosilatruxene, and thiatruxene and isothiatruxene). Systematic studies of these molecules were performed by means of the density functional theory (DFT) and time‐dependent DFT (TD‐DFT) calculations. Electronic excitations (absorption spectra), reorganization energies (hole‐ and electron‐transport properties), electron affinities (EAs), ionization potentials (IPs), hole extraction potentials (HEPs), and electron extraction potentials (EEPs) for all the molecules were reported. Based on the comparative study, it is showed that thiatruxenes (isothiatruxene) are better hole‐transport materials than other truxene (isotruxene) analogs. Abstract : The red‐shifted absorption in asymmetrical isomers are due to destabilization of HOMO and stabilization of LUMO levels. TS, TN, and their corresponding isomers (ITS andITN ) have better charge transport properties than haveT andIT . Smaller IPs of asymmetrical isomers suggest that it is easy to create a hole in these isomers compared with symmetrical isomers.